Jurnal Vokasi STRATEGI PENGEMBANGAN DIGITALISASI UMKM: Bisnis Digital - Riki Nugraha; Anhar Hidayat (Politeknik Bisnis Mayasari, 2022)
Development Strategy for the Digitalization of UMKM in Purbaratu District, Tasikmalaya City. The purpose of this study is to identify and analyze the digitalization development strategy and the priority strategies that can be used by UMKM in Purbaratu District. The research method used is descriptive analysis method. The population in this study were 24 UMKM with various characteristics. The sample of this study used purposive sampling by making criteria and obtained 8 UMKM. The data in this study were obtained from the results of the Disperindag data analysis and observations on 8 UMKM, the analytical technique used was SWOT analysis. Based on the results of data processing, it shows that the calculation of the Internal Factor Analysis Summary (IFAS) is 3.45 and the External Factor Analysis.